Incidence and relative risk of infection with SARS-CoV-2 virus (Covid-19) in European soccer players - Andersen, T. B.; Dahl, A. B.; Carstensen, J. B. (MedRxiv The preprint server for health sciences, 2021)
The purpose of the present study was to investigate the incidence and relative risk of infection with the SARSCoV-2 virus in soccer players. Data from five leagues was used and compared to data from the normal population in each country. Our results revealed that the relative risk was higher in soccer players; in three countries, even when correcting for the estimated true number of infected people in the populations. We discuss that the reason for the higher incidence in soccer players is caused by letting the virus entering a group of players that work closely together.